ANALISIS KOMUNIKASI ANTARBUDAYA ANTARA STAF DAN PELANGGAN DENGAN LATAR BELAKANG BUDAYA YANG BERBEDA DI CITIBANK - Romi Syahril; Azhar Hutomo; priatna priatna (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2023)
This study aims to analyze the literature on intercultural communication that occurs between staff and customers with different cultural backgrounds at Citibank. This study uses a qualitative approach with the literature study method, by collecting data from related journals and articles that discuss intercultural communication in the banking sector. The results of this study will provide an overview of the factors that influence intercultural communication at Citibank, as well as strategies that can be implemented by Citibank staff in improving the quality of communication with customers from different cultural backgrounds